A scoping review protocol to map the research foci trends in tobacco control over the last decade. Issue 1 (28th January 2015) - Halas, Gayle; Schultz, Annette S H; Rothney, Janet; Goertzen, Leah; Wener, Pamela; Katz, Alan
Abstract : Introduction: Tobacco dependence and smoke exposure have been global epidemics with health consequences recognised by the US Surgeon General since the 1960s and 1970s, respectively. During this period, a vast body of research evidence has emerged including many reviews of primary research studies targeting various tobacco control strategies. Published review studies synthesise primary evidence, providing a rich source for mapping the broad range of topics and research foci along with revealing areas of evidence deficits. In this paper, we outline our scoping review protocol to systematically review published review articles specific to tobacco control and primary prevention over the last 10 years. Methods and analysis: Using Arksey and O'Malley's scoping review methodology as a guide, our scoping review of published reviews begins by searching several databases: PubMed, Scopus, the Cochrane Library, the Cumulative Index to Nursing and Allied Health Literature (CINAHL), PsycInfo and the Educational Resources Information Centre (ERIC). Our multidisciplinary team has formulated search strategies and two reviewers will independently screen eligible studies for final study selection. Bibliographic data and abstract content will be collected and analysed using a tool developed iteratively by the research team. Ethics and dissemination: A scoping review of published review articles is a novel approach for examining the breadth of literature regarding tobacco control strategies and, as a secondary analysis, does not require ethics approval. We anticipate results will identify research gaps as well as novel ideas for primary prevention research specific to tobacco control strategies concerning intervention, programming and policy. Although this is our first step in establishing a foundation for a research agenda, we will be disseminating results through journals and conferences targeting primary care providers and tobacco control.